STUDENTS' PERCEPTION ON THE USE OF ENGLISH AS A MEDIUM OF INSTRUCTION: A Case Study at One of Public Senior High Schools in Tanjungpandan Belitung - Haris, Hermiadi (2006)
This research attempts to portray the students' perception on the use of English as a medium of instruction by their teacher in the classroom, and the influence of using English as a medium of instruction on classroom interactions. This research was conducted in one public senior high schools in Tanjungpandan, Belitung, involving 76 eleventh year students from two different classes and two English teachers.The data were collected through interview, journal, and classroom observation. The responses from the interview were transcribed, categorized and interpreted to answer the research questions. The data from the students writing journal were tabulated based on their categories and analyzed to support the finding from interviews. Meanwhile, the data from classroom observation were analyzed and interpreted to examine the influences of using English as a medium of instruction on the classroom interactions.The results from interview showed that 92.10% students in group1, in which English is used 71.4% by the teacher and 84.21% students in group 2, in which English is used 20.5%, had positive perception on the use of English as a medium of instruction. These data were in relevance with the data from students' journals in which 92.10% students in group1 and 88.88% students in group 2 had positive perception on the use of English as a medium of instruction. Meanwhile, the data from classroom observation showed that most students in group 1 were active, serious, and enjoying the teaching and learning process in the classroom. They were also highly appreciative to the teacher. These data were supported by findings from students' interview in which 92.10% students felt positive influences on the use of English as a medium of instruction on the classroom interaction. In-group 2, the students tended to be inactive, not serious, and not enjoying the teaching and learning process. They also had low appreciation to their English teacher. It worth noting that 84.21% students felt positive influences on the use of English as a medium of instruction on the classroom interaction.It is hoped that the findings of this research will help teachers in making decision on whether they should use English or Indonesian as a medium of instruction during teaching and learning process in the classroom. Furthermore, this research can give enlightening information in English teaching and learning to improve the students' mastery in English lesson. In addition, this research may also inspire other researchers to conduct research on other issues in accordance with the use of English as a medium of instruction.